Re-storying trauma through decolonial care in Tracey Lindberg’s Birdie - López-Serrano, Lucía (International Journal of English Studies, 2025)
Tracey Lindberg’s Birdie (2015) tells the story of Bernice Meetoos, a Cree woman with a troubled past, who undertakes a healing dream journey in which she revisits experiences of abandonment and abuse rooted in intergenerational trauma caused by colonialism. In this paper, I suggest that Lindberg’s text reclaims care as a decolonial praxis that generates Indigenous resurgence. Situating care ethics within decolonial and Indigenous relational frameworks, I posit that the forms of care represented in the novel enact re-embodiment, reconfigure kinscapes, and tether personal healing to collective well-being and ecological responsibility. Drawing on Eva Jewell, Leanne Betasamosake Simpson, and Glen Sean Coulthard, the article shows how Birdie aligns care with the regeneration of traditional knowledge and the refusal of heteropatriarchal-capitalist logics. Ultimately, Birdie models resilience as an adaptive, land-based capacity sustained through ceremony and reciprocity, demonstrating that decolonial care foregrounds Indigenous resurgence.